Synthesis and photoisomerization properties of polynorbornenes with azobenzene chromophores - Kang, SH; Shin, HD; Oh, CH; Choi, DH; Park, KH (KOREAN CHEMICAL SOC, 2002)
We successfully synthesized the addition-type polynorbonenes (PNB) exhibiting photochromic properties and excellent thermal stability. Three norbornene-based monomers with different azobenzene moiety (R=NO2, H, OCH3) were synthesized by transesterification method. The corresponding PNB copolymers were synthesized by transition metal-catalyzed addition polymerization method, and characterized by GPC, UV-Vis spectroscopy, NMR, and thermal analysis. For comparison of the photochromic properties depending on the rigidity of polymer backbone, we prepared the polymethylmethacrylate (PMMA) copolymer with the corresponding azobenzene moiety. We investigated the photoisomerization behavior by means of optical muitichannel analyzer with Xe lamp as well as real-time UV-Vis spectroscopy with high-pressure mercury lamp. Among three PNB copolymers, a polymer with azobenzene (R=H) was the most adaptable for observation of photoisomerization behavior. It was found that the rate of photoisomerization and relaxation depended on the structure of azobenzene chromophore, rather than that of polymer backbone.
Keywords: LIQUID-CRYSTALLINE POLYMERS; ISOTHERMAL PHASE-TRANSITION; BENZOATE SIDE-CHAINS; ISOMERIZATION; POLYESTERS; RESIDUES; BACKBONE; UNITS; DYES